Implementation, usage, and effectiveness of Ghana climate change policies: an assessment of the national CSA Action Plan and CSA Investment Framework - Djido, Abdoulaye; Segnon, Alcade C; Botchway, Vincent Ansah; Karbo, Naaminong; Sam, Kingsley Odum; Essegbey, George Owusu; Nutsukpo, Delali; Asafu-Adjaye, Nana Yamoah; Agyemang, Kingsley; Whitbread, Anthony M.; Thornton, Philip K.; Zougmoré, Robert B. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
" Five years after the adoption of CSA Action Plan, followed by a CSA Investment Framework, it was crucial to assess the level of implementation and usage and draw lessons on the effectiveness of these two policy documents. This study aims to provide a scientific-based assessment of the level of implementation, usage, and effectiveness of the above-mentioned two Ghana climate change policy documents. Due to low awareness of stakeholders, the implementation of the CSA Action Plan and CSA Investment Framework is low (19% of studied districts). The usage of the CSA Action Plan focuses more on crop value chain development followed by livestock and fish value chains. The CSA Investment Framework was used to mobilize resource to develop climate-resilient cropping systems, alternative livelihood systems, post-harvest management, market systems, and water conservation activities. The effectiveness of the CSA Action Plan and CSA Investment Framework depends on the number of target beneficiaries, budget allocation and funds mobilized. Multipurpose policy instruments are critical for bringing about a conducive environment to address climate change and related risks. Increasing awareness of the CSA Action Plan is a key pathway to enhance its usage, implementation and effectiveness across scales. To enable effective use of the CSA Investment Framework, there is a need to enhance the capacity of key stakeholders on the development of bankable proposals